Analysis of Enterohepatic Circulation of a Drug after Intravenous with Time-lag - Avinash.H, Lakshmi Naryana. K (International Journal of Advanced Science and Technology, 2020)
A mathematical model is constructed to understand the time lag in the pharmacokinetics of Enterohepatic flow of drug with intravenous administration. Laplace Transform Tecnique is used to discover the solutions of nonlinear differential equations constructed by the flow of drug with excretion and reabsorption in the primary and secondary compartments after intravenous administration Matlab is used to draft the plasma level profiles according to the experimental data.